Expanding the phenotype of spastic paraplegia 26: Report of 4 cases with hearing dysfunction - Carolina Lopes; Fernando Silveira; Goreti Nadais; Miguel Leão (Annals of Musculoskeletal Medicine - Peertechz Publications, 2019)
Background: Spastic Paraplegia 26 (SPG26) is a complex type of spastic paraplegia caused by B4GALNT1 gene pathogenic variants, and is characterized by childhood/adolescence onset of progressive spastic paraplegia associated with mild to moderate cognitive impairment and developmental delay, dysarthria, cerebellar ataxia, and peripheral neuropathy.  Results: We report four additional cases, from three Portuguese families, of SPG26, demonstrating high phenotypic heterogeneity, both inter-familial and intra-familial. Using neurophysiological studies, we describe hearing dysfunction as a feature of SPG26.  Conclusions: SPG26 is rare and familiarity with the typical presentation may be helpful to the diagnosis and allow an increased awareness of this disorder.